Measuring implementation outcomes: An updated systematic review of measures’ psychometric properties - Mettert, Kayne; Lewis, Cara; Dorsey, Caitlin; Halko, Heather; Weiner, Bryan (Implementation research and practice, 2020)
Background: Systematic reviews of measures can facilitate advances in implementation research and practice by locating reliable and valid measures and highlighting measurement gaps. Our team completed a systematic review of implementation outcome measures published in 2015 that indicated a severe measurement gap in the field. Now, we offer an update with this enhanced systematic review to identify and evaluate the psychometric properties of measures of eight implementation outcomes used in behavioral health care. Methods: The systematic review methodology is described in detail in a previously published protocol paper and summarized here. The review proceeded in three phases. Phase I, data collection, involved search string generation, title and abstract screening, full text review, construct assignment, and measure forward searches. Phase II, data extraction, involved coding psychometric information. Phase III, data analysis, involved two trained specialists independently rating each measure using PAPERS (Psychometric And Pragmatic Evidence Rating Scales). Results: Searches identified 150 outcomes measures of which 48 were deemed unsuitable for rating and thus excluded, leaving 102 measures for review. We identified measures of acceptability (N = 32), adoption (N = 26), appropriateness (N = 6), cost (N = 31), feasibility (N = 18), fidelity (N = 18), penetration (N = 23), and sustainability (N = 14). Information about internal consistency and norms were available for most measures (59%). Information about other psychometric properties was often not available. Ratings for internal consistency and norms ranged from “adequate” to “excellent.” Ratings for other psychometric properties ranged mostly from “poor” to “good.” Conclusion: While measures of implementation outcomes used in behavioral health care (including mental health, substance use, and other addictive behaviors) are unevenly distributed and exhibit mostly unknown psychometric quality, the data reported in this article show an overall improvement in availability of psychometric information. This review identified a few promising measures, but targeted efforts are needed to systematically develop and test measures that are useful for both research and practice. Plain language abstract: When implementing an evidence-based treatment into practice, it is important to assess several outcomes to gauge how effectively it is being implemented. Outcomes such as acceptability, feasibility, and appropriateness may offer insight into why providers do not adopt a new treatment. Similarly, outcomes such as fidelity and penetration may provide important context for why a new treatment did not achieve desired effects. It is important that methods to measure these outcomes are accurate and consistent. Without accurate and consistent measurement, high-quality evaluations cannot be conducted. This systematic review of published studies sought to identify questionnaires (referred to as measures) that ask staff at various levels (e.g., providers, supervisors) questions related to implementation outcomes, and to evaluate the quality of these measures. We identified 150 measures and rated the quality of their evidence with the goal of recommending the best measures for future use. Our findings suggest that a great deal of work is needed to generate evidence for existing measures or build new measures to achieve confidence in our implementation evaluations.